Preparation of magnetic kaolinite composite for lead removal in aqueous solution / Izzan Salwana Izman - Izzan Salwana, Izman (2019)
Magnetic kaolinite composite was successfully synthesized using combination of kaolinite and iron oxide through co-precipitation method. The synthesized kaolinite-iron oxide (Kao-IO) and raw kaolinite (Kao) was characterized by using X-ray diffractometer (XRD), scanning electron microscope (SEM), and fourier- transform infrared spectroscopy ATR type (FTIR ATR). The Kao-IO composite was used to remove Pb2+ from aqueous solution through adsorption studies under various experimental conditions (pH, contact time, initial concentration of Pb solution, and temperature). Meanwhile the Pb desorption studies of Pb loaded Kao- IO were performed with different desorbing agents. The optimum experimental condition was achieved at pH 6, reaction time of 120 min at initial concentration ranged from 10 to 70 ppm. Kao-IO composite has higher adsorption capacity (30.93 mg g-1) compared to Kao (25.04 mg g-1). EDTA was the best desorbing agent with the highest desorption efficiency (39.18%). Overall, Kao-IO composite demonstrated high potential as suitable adsorbent to treat Pb contaminated water.